From Soccer Chant to Sonic Meme: Sound Politics and Parody in Argentina’s “Hit of the Summer” - O’Brien, Michael S. (MUSICultures, 2020)
In early 2018, a protest chant against Argentine President Mauricio Macri became so widespread that journalists called it the “hit of the summer.” Originating in soccer stadiums, it soon spread in other formats as musicians transformed it into countless parody videos in a process I call a “sonic meme.” This involved first transforming mass culture (a march) into vernacular practice (a soccer chant), and then transforming that chant, in turn, back into mass-mediated popular music. The latter process was parodic not in the sense of profaning high culture, but rather transformed the already profane into the higher prestige register of music-as-art or music-as-commodity.